2020
DOI: 10.1155/2020/1892375
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Literature-Based Knowledge Database and Expression Data to Explore Molecular Pathways Connecting PPARG and Myocardial Infarction

Abstract: Peroxisome proliferator-activated receptor γ (PPARG) might play a protective role in the development of myocardial infarction (MI) with limited mechanisms identified. Genes associated with both PPARG and MI were extracted from Elsevier Pathway Studio to construct the initial network. The gene expression activity within the network was estimated through a mega-analysis with eight independent expression datasets derived from Gene Expression Omnibus (GEO) to build PPARG and MI connecting pathways. After that, gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…PPARG is a member of the nuclear hormone receptor superfamily, which can recruit transcriptional coactivators necessary to initiate the transcription of target genes and may also play a protective role in the development of MI 34,35 . At the same time, Cao et al also con rmed that THERE was a signi cant correlation between PPARG and protection of MI 36 .…”
Section: Discussionmentioning
confidence: 90%
“…PPARG is a member of the nuclear hormone receptor superfamily, which can recruit transcriptional coactivators necessary to initiate the transcription of target genes and may also play a protective role in the development of MI 34,35 . At the same time, Cao et al also con rmed that THERE was a signi cant correlation between PPARG and protection of MI 36 .…”
Section: Discussionmentioning
confidence: 90%
“…Yy1 heterozygous mice exhibit growth retardation, neurulation defects, intellectual disability, and brain abnormalities [53,55]. PPARG regulates circadian cardiovascular rhythms and appears to have a cardioprotective effect [56][57][58]. PAX6 regulates the development of the central nervous system, and a patient with mental disorder had a deletion in the adjacent region of this gene [59][60].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous evidence has suggested that PPARG may be a risk factor for cardiovascular diseases such as metabolic syndrome, obesity, diabetes and hypertension 34 37 . PPARG is a member of the nuclear hormone receptor superfamily, which can the recruit the transcriptional coactivators necessary to initiate the transcription of target genes and may also play a protective role in the development of MI in many studies 38 – 39 . At the same time, previous studies have also found that PPARG may play an important role in the pathophysiological mechanism of OSA 40 , 41 , and qPCR detection suggests that the expression of PPARG in OSA patients is significantly different from that in the control group 42 .…”
Section: Discussionmentioning
confidence: 99%